Peruvian plant resources as potential natural controllers of adult Aedes aegypti - Cordova Paz Soldan, Ofelia Magdalena (2023)
Aedes aegypti is an important vector of tropical diseases like Dengue, Zika, Chikungunya, and Yellow Fever and affects mainly countries located in tropical and subtropical zones, including Peru. Synthetic insecticides are used to control this vector, but they also cause a residual effect on the environment, whereas the vector has developed resistance to these compounds, so there is a current need to search for new control alternatives, such as the use of abundant natural resources. Therefore, this work aimed to evaluate the biocidal activity of extracts and oils from Cymbopogum citratus, Rosmarinus officinalis, and Minthostachys mollis on adult Aedes aegypti, as well as to evaluate their quality parameters. Furthermore, the chemical profile of the three species was assessed by ultra-high-performance liquid chromatography coupled with mass spectrometry (LC-MS/MS). The results showed that the aqueous/ethanolic extracts and the essential oils from the three evaluated species presented a biocidal effect on adult A. aegypti. Regarding the analysis of the chemical profile, 15 compounds were identified in R. officinalis, while 29 compounds were identified from C. citratus and 30 compounds from M. mollis. Moreover, the extracts and oils presented quality parameters according to standards. In conclusion, the biocidal potential of the C. citratus, R. officinalis, and M. mollis on A. aegypti adults was reported so that they can be seen as a real natural alternative for the control of tropical diseases transmitted by this vector so that plant products are more eco-friendly and subject to lower resistance by target organisms.